Μπορεί κάποιος να επαληθεύσει αυτό; (cotx-1) / (cotx + 1) = (1-sin2x) / (cos2x)

Μπορεί κάποιος να επαληθεύσει αυτό; (cotx-1) / (cotx + 1) = (1-sin2x) / (cos2x)
Anonim

Απάντηση:

Επαληθεύεται παρακάτω:

Εξήγηση:

# (1-sin2x) / (cos2x) #

# = (sin ^ 2x + cos ^ 2x-2sinxcosx) / (cos2x) #Οπως και.#color (καφέ) (sin2x = 2sinxcosxandsin ^ 2x + cos ^ 2x = 1) #

# = (cosx-sinx) ^ 2 / (cos ^ 2x-sin ^ 2x) #Οπως και,#color (μπλε) (cos2x = cos ^ 2x-sin ^ 2x) #

(cosx-sinx)) (cosx-sinx)) / (ακύρωση ((cosx-sinx)

= (ακυρώνω (cosx / sinx-1)) / (cancelsinx (cosx / sinx + 1)) #

# = (cotx-1) / (cotx + 1) #Επαληθευμένη.